Clinical evaluation of i-step qualitative heart-specific fatty acid binding protein (h-fabp) test (cardiodetect®) and quantitative cardiac troponin t, for the diagnosis of acute myocardial infarction in the emergency department - Ab Rahman, Nik Hisamuddin Nik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Objective To assess the diagnostic indices of the CardioDetect assay and the quantitative cardiac troponin T test, in diagnosing AMI in the ED, according to the time of onset of chest pain. Methodology A total of eighty eligible patients presenting with ischemic type chest pain with duration of symptoms within the last 36 hours were enrolled. All patients were tested for H-FABP and Troponin T at presentation to ED. A repeated Cardiodetect test was performed one hour after the initial negative result, and a repeated Troponin T test was also performed 8- 12 hours after an initial negative result. The diagnostic indices [sensitivity, specificity, positive predictive value, negative predictive value, receiver operating curve (ROC)] were analysed for CardioDetect and Troponin T (individually and in combination), and also for the repeat CardioDetect test. Data entry and analysis was performed using SPSS version 12.0 and analyse-it software. Results The CardioDetect test was more sensitive and had a higher NPV than troponin T (TnT) test during the first 12 hours of onset of chest pain. The repeat CardioDetect had better sensitivity and NPV than the initial CardioDetect. The sensitivity and NPV of the combination test (CardioDetect and troponin T) was also superior to the each test performed individually. Conclusion CardioDetect test is more sensitive and has a better NPV than Troponin T during the first 12 hours of AMI. It may be used to rule out myocardial infarction during the early phase of ischemic chest pain.